FE-LEAD : AN EXPLORATION STUDY TO CREATE FUTURE LEADERS IN GOVERNMENT AGENCY THROUGH TALENT MANAGEMENT - Haziroh, Awanis; Putra, Febrianur; Christi, Martha; Demircioglu, Aytekin (Universitas Muhammadiyah Surakarta, 2023)
This research aims to explore an integrated model related to mechanisms or operational standards for the leadership succession planning system through developing talent management theory and analyzing Indonesian Government Agencies that can be involved in implementing the succession planning system. The research is qualitative through comparative studies and literature reviews in the form of regulations related to managing state civil servants (ASN) using an exploratory, and descriptive analysis method. The findings in this research are that the government can optimally implement the operational mechanisms or standards to build an integrated succession planning system through talent management in each government agency. The results of this research recommend that the succession planning system be an urgent element to be realized immediately and to create future leaders who are professional, dignified, and able to become the central axis in the wheels of a future government.